Where the wild things bite ebook - Harper, Molly (Half-Moon Hollow, 2016)
In Molly Harper's witty new paranormal romance, a rare-book expert is delivering a package to Half Moon Hollow when her plane goes down, and a sexy vampire comes to her rescue. He's clearly got ulterior motives, but does he want to date her...or devour her? Delivering a rare book to a valued customer is definitely part of mild-mannered archivist Anna Whitfield's job description. You know what isn't? Protecting her precious cargo from mid-flight theft by the very pilot who is flying her to Half-Moon Hollow... while trying to appear as unappetizing as possible to the only other passenger, a vampire. Undead bookstore owner Jane Jameson could be waiting a very long time for her book. Possibly forever. Fortunately, Anna's dashing fanged companion Finn Palmeroy helps her fend off the attack, but not before their plane crash lands in the forest hundreds of miles from civilization. Great, now she's stranded with a priceless tome and a rakish vampire whose bedtime is fast approaching. Why does everyone want this book so badly, anyway? Anna just wants to get it to Jane before Finn decides to turn her into dinner—or sweep her off her feet. Okay, the second option is really tempting . But they're not out of the woods yet...